Treatment technology of shale gas fracturing flowback fluid: a mini review - Zhao, Tianbiao (Frontiers in Energy Research, 2023)
Shale gas fracturing flowback fluid, characterized by its large volume, complex composition, and potential adverse environmental impacts, has gradually become one of the problems affecting the large-scale development of shale gas resources. Failure to effectively address the treatment of fracturing flowback fluid will severely constrain shale gas development. This paper focuses on the treatment technologies for shale gas fracturing flowback fluid, discussing its water quality characteristics and summarizing the research progress in physical technology, chemical technology, biological technology, and combined technology. Development recommendations are also provided. The results show that shale gas fracturing flowback fluid exhibits characteristics such as complex composition, high viscosity, and high emulsification, and difficult to treat. Individual physical technology, chemical technology, or biological technology is effective in removing certain pollutants from the flowback fluid. Moreover, the combined use of these treatment technologies prove more effective in achieving reuse or discharge standards. With the continuous expansion of shale gas development and increasingly stringent environmental protection requirements worldwide, the volume of flowback fluid requiring treatment is continuously rising. By developing energy-efficient and emission-reduction treatment technologies, and actively recycling and utilizing resources and energy, and adopting clean fracturing fluid system, efficient, energy-saving, environmentally friendly, and economically viable treatment for shale gas fracturing flowback fluid can be achieved.